(untitled) (Biological Sciences - PJSIR, 2001)
The adsorption of Cd, Cu, Pb, Ni and Zn ions on maize (Zea mays) stalk meal was examined by equilibrium studies at 29°C. The amounts ofthe metal ions removed from solution depended on the meta! ion type, the ionic size of the metals and were enhanced by EDTA (%N=12.05) modification of the cellulosic sorbent. The sorption coefficient, Kd’ of the meta! ions between the absorbent phase and the bulk aqueous phase was found. The sorption data fitted the Langmuir isotherm equation and the maximum meta! ion binding capacities, Xm of20.5 mg goland 9.2 mg g’ for Cd (II), and of12.2 mg goland 7.0 mg g’ for Cu (II) on EDTA modified and unmodified maize stalk meal were determined. This modification amounts to an increase of 44.87% and 57.38% for Cd (11)and Cu (II) ions adsorbed respectively. Ni (II), Zn (11)and Pb (11)ions showed Xm of2.5 mg g’, 4.3 mg g’ and 20.3 mg g’ for the unmodified sorbent respectively. The sorption on the unmodified sorbent of lead ions from solutions containing zinc ions shows that lead ions are preferentially removed from solution.